2000
DOI: 10.1002/(sici)1521-3765(20000103)6:1<54::aid-chem54>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A New Organic Nanoporous Architecture: Dumb-Bell-Shaped Molecules with Guests in Parallel Channels

Abstract: A new type of dumb-bellshaped host molecule (6 ± 8) has been synthesised, of which 1,8-bis((1)-adamantyl)-1, 3,5, forms an open porous architecture when cocrystallised with a number of typical solvent molecules. Adamantyl substituents attached to a tetraalkyne spacer build up the walls of parallel channels wherein guest molecules are aligned. Surprisingly, the tetraalkyne unit is significantly bent. Desolvation experiments provide evidence for a reversible inclusion of guests. In the case of the inclusion of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Removal of the acetone protecting group was effected by treatment with KOH at high temperature, yielding adamantyl diyne 12 . Although dimerization of monoyne 4 under Hay conditions proved difficult, the dimerization of diyne 12 proceeded efficiently, giving tetrayne 1c as a crystalline white solid in quantitative yield …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the acetone protecting group was effected by treatment with KOH at high temperature, yielding adamantyl diyne 12 . Although dimerization of monoyne 4 under Hay conditions proved difficult, the dimerization of diyne 12 proceeded efficiently, giving tetrayne 1c as a crystalline white solid in quantitative yield …”
Section: Resultsmentioning
confidence: 99%
“…The stability of tert ‐butyl‐endcapped polyynes suggested that a variation of this structure might be a viable target, that is, the adamantyl group ( 1a , 1b , 1c , 1d , 1e , 1f , 1g , 1h , 1i , 1j ). Although 1c has been studied quite substantially as a substrate for solid‐state host guest systems, little is known about the electronic and structural aspects of other members of this series. We report herein on the synthesis of 1a , 1b , 1c , 1d , 1e , 1f , 1g , 1h , 1i , 1j and their physical and spectroscopic characterization.…”
Section: Introductionmentioning
confidence: 99%
“…[5d,e, 8±10, 12±14, 22c] As polymerization of polyacetylenic compounds can be considered as a function of the distance between such molecules, [11] we consequently decided to build up dumb-bell-shaped systems ( Figure 2) where the carbon chains are kept at a distance by bulky, spherical end groups. [28,29] For this purpose, dendrimers [30] seemed to be the most suitable choice. Ideally, they are perfect monodisperse macromolecules with a regular and highly branched three-dimensional architecture, such as Fre ¬ chet×s aromatic polyether dendrimers which are easily accessilbe through convergent procedures.…”
Section: Resultsmentioning
confidence: 99%
“…In the last step, 29 and 28 were obtained without any losses by the cleavage of the silylic OH protecting groups. As we were unsure about the kinetic stability of the 3,5-dihydroxyphenylacetylene (28) under the following basic reaction conditions (Scheme 4), we worked towards for the TIPS protected derivative 29, in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, nanoporous materials are crystalline framework solids, such as zeolites, discotic molecular assemblies, [31][32][33] or "robust" molecular crystals formed using supramolecular [38] design principles. [2,[11][12][13][14][15][16][17][18][19][20] These materials can have large void volumes and high internal surface areas, but the supramolecular materials often tend to collapse upon emptying the pores. Several approaches have also been presented to prepare mesoporous and macroporous materials, such as "track-etching", [4][5][6] using honeycomb structures, [27][28][29] and emptying nanostructured templates (e.g., sol-gel processing of surfactants or block copolymers, [7][8][9][10] selective degradation of material with UV exposure, [24][25][26] pyrolysis, [21][22][23]34] and selective removal of lowmolecular-weight amphiphiles (combs) from hierarchically self-assembled polymeric comb-coil supramolecules [35,36] ).…”
mentioning
confidence: 99%